Volume 4: 20th Design for Manufacturing and the Life Cycle Conference; 9th International Conference on Micro- And Nanosystems 2015
DOI: 10.1115/detc2015-46355
|View full text |Cite
|
Sign up to set email alerts
|

Design for Fused Filament Fabrication Additive Manufacturing

Abstract: In this paper, we explore the topic of Fused Filament Fabrication (FFF) 3D-printing. This is a low-cost additive manufacturing technology which is typically embodied in consumer-grade desktop 3D printers capable of producing useful parts, structures, and mechanical assemblies. The primary goal of our investigation is to produce an understanding of this process which can be employed to produce high-quality, functional engineered parts and prototypes. By developing this understanding, we create a resource which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…They concluded that FFF parts routinely showed the poorest dimensional precision compared to other AM processes. The FFF literature is replete with studies on the effect of the process parameters on the surface roughness and strength of the parts [14][15][16][17], but few on dimensional variation.…”
Section: Review Of the Related Researchmentioning
confidence: 99%
“…They concluded that FFF parts routinely showed the poorest dimensional precision compared to other AM processes. The FFF literature is replete with studies on the effect of the process parameters on the surface roughness and strength of the parts [14][15][16][17], but few on dimensional variation.…”
Section: Review Of the Related Researchmentioning
confidence: 99%
“…The bene ts of AM, in offering exibility in design (opening up the pathway to light-weight internal structuring and for part consolidation [8]), and tool-less manufacture (removing the cost burden and extensive lead-time for tooling, especially for low volume manufacture as within the aerospace and niche vehicle land-transport sectors [9]). These capabilities make it a very attractive proposition for these sectors, but uptake has been limited to date due to the poor mechanical properties that are obtained from the polymers [10], with, until relatively recently, no capability for improving mechanical properties through their reinforcement using long or continuous bres.…”
Section: Introductionmentioning
confidence: 99%
“…However, widespread adoption of FFF for commercial production is still limited. Several limitations are theorized to be reasons driving down commercial demand: long print times [11], coarse surface finish [12], coarse geometric resolution [13], low interlayer bonding strength [14]- [16], and highly anisotropic behavior [17]- [21]. Nonetheless, there are certain applications where FFF is a better fit; for example, the International Space Station operates a FFF machine because it can work in microgravity, the feedstock is relatively nonhazardous, and the printed parts are recyclable [22], [23].…”
Section: Introductionmentioning
confidence: 99%